Economic Feasibility Study of the Multi-Utility Tunnel (MUT) Project in the New Capital City of Nusantara (IKN) During the Budget Efficiency Period - Fauzan Kurnianto; Bambang Endro Yuwono (Eduvest - Journal of Universal Studies, 2026)
The development of Ibu Kota Nusantara (IKN) has faced considerable uncertainty following the implementation of government budget efficiency policies in 2025, which may affect the feasibility of key infrastructure, including the Multi-Utility Tunnel (MUT). This study aims to evaluate the feasibility of MUT development under budget efficiency conditions by analyzing its economic, social, and environmental dimensions to support informed decision-making by relevant stakeholders. The Life Cycle Cost (LCC) method is applied using structural design data and applicable regulations, while project implementation is assessed through scenario-based simulation and forecasting. Economic feasibility is analyzed using Net Present Value (NPV) and sensitivity analysis, whereas social and environmental impacts are evaluated through systematic observation. The analysis identifies three possible development scenarios: optimistic, moderate, and pessimistic. The moderate scenario exhibits the highest initial and operational costs when cash inflows are excluded. To achieve economic feasibility at an NPV of zero, the pessimistic scenario requires the highest total cash inflow, amounting to IDR 1.074 trillion during the operational phase. Among the three variables analyzed, initial cost is the most sensitive parameter, recording the highest sensitivity value of 24.34 under both the pessimistic and moderate scenarios. In contrast, the discount rate is the least sensitive variable, with a sensitivity value of −9.00 across all scenarios. In terms of social impact, budget efficiency may affect public trust in the project, while environmentally, it may reduce immediate adverse impacts but risk prolonging long-term environmental effects.